Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jwmg.21402
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term herpetofaunal response to repeated fuel reduction treatments

Abstract: Fuel reduction treatments are used to reduce wildfire risk and to restore plant communities. Yet, repeated mechanical or prescribed fire treatments may gradually change forest structure and microhabitat conditions, favoring some taxa and decreasing suitability for others. We experimentally assessed long‐term (intermittent years, 2003–2016) effects of repeated dormant‐season mechanical and prescribed fire treatments on capture rates of reptiles and amphibians in southern Appalachian upland hardwood forests. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Even for wildlife taxa thought to be vulnerable to the effects of fire, such as some herpetofauna, previous studies did not observe negative responses to fire for these species, and fire contributed to greater herpetofaunal diversity over large spatial and temporal scales (Hossack and Corn , Greenberg et al. ). However, some taxa may respond to fire severity and time since fire in unique ways (e.g., small mammals), warranting study of the pyrodiversity–biodiversity relationship across a range of taxa and environmental conditions (Zwolak and Foresman ).…”
Section: Discussionmentioning
confidence: 91%
“…Even for wildlife taxa thought to be vulnerable to the effects of fire, such as some herpetofauna, previous studies did not observe negative responses to fire for these species, and fire contributed to greater herpetofaunal diversity over large spatial and temporal scales (Hossack and Corn , Greenberg et al. ). However, some taxa may respond to fire severity and time since fire in unique ways (e.g., small mammals), warranting study of the pyrodiversity–biodiversity relationship across a range of taxa and environmental conditions (Zwolak and Foresman ).…”
Section: Discussionmentioning
confidence: 91%
“…This FFSS site is one of the few that remain active, having been treated with a total of 4 dormant-season prescribed burns and 2 mechanical treatments through 2016 [31]. Our study is based on vegetation changes following the four management treatments: dormant season prescribed burning in February or March, using either aerial ignition (spot fire) or strip head fire techniques (B) (4 total: 2003, 2006, 2012, and 2015); mechanical felling all woody stems >1.8 m tall and <10 cm in diameter, and all shrubs of any height in December-February (M) (2 total: 2001-2002, and 2012); a combination of dormant season burning and mechanical treatment (MB) (4 B: 2003, 2006, 2012, and 2015; 2 M: 2001-2002, and 2012); and no treatment to compare the results of each treatment (C) ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Much of what we know about amphibian responses to fire disturbance stems from studies of prescribed fire. While prescribed fires are different from wildfire in that they typically burn at a lower, more uniform intensity (Arkle and Pilliod 2010, Greenberg et al 2018, Jacobsen et al 2020), studies focused on responses to prescribed fire are an important foundation for understanding the nuanced effects of fire on amphibians. For example, Ford et al (1999) reported no difference in salamander abundance between sites with prescribed burning and control riparian forests in our study region.…”
Section: Discussionmentioning
confidence: 99%